The Evaluation of “APROMED” Application Based on Organizational Assesment - Miliani, Okta; Gde Wahyu Mahatma Putra, Dewa Ngakan (jitek, 2023)
Developing an outpatient reservation application is one of the efforts to fulfil the requirements of PMK RI Number 21 of 2020. Kaliwates General Hospital has an outpatient reservation application called APROMED. However, 7.3 more times patients made reservations manually than using APROMED, and the decrement in APROMED users is 3.2–5.6% monthly. Personally, the informant wanted an APROMED usage level above 50%, but it was only 13.6%. Based on these data, the problem is the low usage level of APROMED. This research aimed to evaluate the APROMED application based on an organizational assessment at Kaliwates General Hospital because a thorough evaluation had never been done. The method used was descriptive research with the cross-sectional study by measuring based on the success components of the DeLone and McLean systems using the ISO/IEC 15504 measurement scale. The results obtained were 76.9% 'L' largely achieved for system quality value, 52% 'L' largely achieved for information quality, 73.9% 'L' largely achieved for service quality, 32% 'P' partially completed for user satisfaction, and 51.8% 'L' largely achieved for net benefits. Kaliwates General Hospital must support APROMED application development based on evaluation, research, development, trial, and implementation activities.